Mitochondrial Biogenesis Drives a Vicious Cycle of Metabolic Insufficiency and Mitochondrial DNA Deletion Mutation Accumulation in Aged Rat Skeletal Muscle Fibers - Herbst, Allen; Johnson, Chad J.; Hynes, Kayla; McKenzie, Debbie; Aiken, Judd M. (PLOS ONE, 2013)
Aged muscles possess dysfunctional fibers that contain intracellular expansions of somatically derived mitochondrial DNA deletion mutations. At high abundance, these mutations disrupt the expression of mitochondrially-encoded protein subunits of the electron transport chain resulting in aerobic respiration deficient muscle fiber segments. These fiber segments atrophy and break contributing to the loss of muscle mass and function that occurs with age. By combining micro-dissection of individual muscle fibers with microarray analysis, we observed the response induced within these abnormal muscle fibers and detected an increase in many genes affecting metabolism and metabolic regulation. The transcriptional profile and subsequent protein validation suggested that a non-compensatory program of mitochondrial biogenesis was initiated. We hypothesized that this non-adaptive program of mitochondrial biogenesis was driving mtDNA deletion mutation accumulation. We tested this hypothesis by treating aged rats with β-Guanidinopropionic acid, a compound that stimulates mitochondrial biogenesis. β-Guanidinopropionic acid treatment increased muscle mitochondrial genome copy number and resulted in a 3.7 fold increase in the abundance of electron transport chain negative muscle fiber segments. We conclude that in electron transport system abnormal muscle fiber segments, a vicious cycle of metabolic insufficiency and non-compensatory mitochondrial biogenesis drive mtDNA deletion mutation accumulation.